2021
DOI: 10.1021/acs.jpclett.1c02876
|View full text |Cite
|
Sign up to set email alerts
|

High Anisotropic Optoelectronics in Two Dimensional Layered PbSnX2 (X = S/Se)

Abstract: We systematically study the giant anisotropic optoelectronics in layered PbSnX2 (X = S/Se). The highly anisotropic optoelectronics mainly originates from the asymmetric sublattices SnX, resulting in the anisotropy of photoelectronic properties with fascinating visible light absorption range in single-layer and bilayer PbSnX2. We employ uniaxial strain in both the x and y directions and find an indirect-to-direct band gap transition, while the quasiparticle indirect band gap presents excellent linear scaling wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…1b , the flake exhibits semiconducting behaviors. Xu et al 10 have shown that PbSnSe 2 exhibits semiconducting behaviors if the number of layers in the flake is less than 8. Therefore, we suggest that the number of layers in the flake should be less than 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b , the flake exhibits semiconducting behaviors. Xu et al 10 have shown that PbSnSe 2 exhibits semiconducting behaviors if the number of layers in the flake is less than 8. Therefore, we suggest that the number of layers in the flake should be less than 8.…”
Section: Resultsmentioning
confidence: 99%
“…2d shows that the value of the dielectric constant for PbSnSe 2 in the temperature range of 150 K–220 K is approximately 1.4, which is much close to the values of the dielectric constant found for the ternary compound. 10 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other fascinating properties drive the interest of the community to search for more compositions and crystal structures that can form Janus 1D nanotubes with small radii and novel properties arising from the spontaneous wrapping of the 2D sheet into a tube. The class of 2D group IV–IV monochalcogenides (as illustrated in Figure a) show strong mechanical and electronic anisotropy and giant in-plane spontaneous polarization, ,, and have properties interesting for electronic and optoelectronic applications, Their Janus form, e.g., PbSnS 2 , has recently emerged and brought new perspectives for electronic, thermoelectric, supercapacitors, and optoelectronics devices. …”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental evidence suggests that ultrathin (2.4 nm) PbSnS 2 sheets possess not only a large anisotropic photoresponse but also highly anisotropic hole mobility synthesized by the chemical vapor deposition (CVD) method. 27,28 Furthermore, the synthesized layered SnP 2 S 6 exhibits excellent photosensitive capabilities in addition to its rich piezoelectric properties and ionic conductivity. 29,30 It has been investigated that the synthesized ternary compounds exhibit not only a favorable band gap and carrier mobility but also high stability, and their variable stoichiometric ratios lead to the construction of abundant 2D optoelectronic materials.…”
Section: Introductionmentioning
confidence: 99%